The Educational and Developmental Psychologist (Cambridge)
Published biannually, this quality, peer-reviewed journal publishes psychological research that makes a substantial contribution to the knowledge and practice of education and developmental psychology. The broad aims are to provide a vehicle for dissemination of research that is of national and international significance to the researchers, practitioners and students of educational and developmental psychology.
Keywords: Psychology